MiR-205 mediated APC regulation contributes to pancreatic cancer cell proliferation - Qin, Rui-Feng (World J Gastroenterol, 2019)
BACKGROUND: Pancreatic cancer is a deadly malignancy with aggressive properties. MicroRNAs (miRNAs) participate in the pathogenesis of a variety of diseases and molecular processes by targeting functional mRNAs. Nevertheless, the regulatory role of miRNAs in signaling pathways involved in pancreatic cancer remains largely unknown. AIM: To explore the molecular regulation involved in pancreatic cancer and potential mechanisms of miR-205. METHODS: Microarray analysis was performed to investigate the expression profile of miRNAs in pancreatic cancer. Expression of miR-205 was validated by qRT-PCR. Target prediction and functional enrichment analysis were employed to seek potential target genes of miR-205 and potential functions of these genes. The target binding of miR-205 and adenomatous polyposis coli (APC) was validated by luciferase reporter assay. APC protein expression in pancreatic cancer was validated by qRT-PCR and Western blot. Proliferation was evaluated by MTT and colony formation assays. RESULTS: A large number of miRNAs with altered expression were identified in pancreatic cancer. MiR-205 was significantly up-regulated. APC was found to be a validated target of miR-205 and down-regulated in pancreatic cancer. Proliferation experiments showed that miR-205 could promote cell proliferation in pancreatic cancer by targeting APC. CONCLUSION: The above findings suggested that miR-205 mediated APC regulation contributes to pancreatic cancer development, which could be considered as a novel prognostic biomarker for clinical care.